How professional ethics impact construction quality: Perception and evidence in a fast developing economy - Abdul-Rahman, H.; Wang, C.; Yap, X.W. (Academic Journals, 2010)
There is a perception that majority of quality-related issues are caused by human factors. The issue of professional ethics plays an important role in quality-related problems in a construction project. This paper highlights the current level of professional ethics standard in the construction industry and how ethics influences the quality of construction projects. A questionnaire survey was conducted in the construction industry in Malaysia, a fast developing economy. Results indicate that various forms of unethical conducts have significant impact on construction quality. This study concludes that professional ethics is a pre-requisite to attaining sustained and acceptable quality in construction and suggests several approaches to enhance professionalism among construction professionals to improve quality in construction.